Pencegahan Dini Karies Gigi Anak Dengan Fissure Sealant Pada Siswa Sekolah Dasar - Rianne Rollin Pangau; Fione Vesty Logor; Oksfriani Jufri Sumampouw (Universitas, 2024)
Dental caries is experienced by 60-90% of children in many countries, both developing and industrialized countries. Riskesdas 2018 shows that the prevalence of caries in Indonesia in 2018 reached 45.3%. This condition shows that the prevalence of caries in Indonesia, both adults and children, is still high. One preventive measure to prevent dental caries is to apply fissure sealant to teeth that have deep pits and fissures. The objective this activity to provide education and application for preventing dental caries in children aged 6-7 years. This activity is carried out through several stages, namely preparation, data collection, problem identification, and implementation of activities. The result showed that the target caries index for primary teeth (deft) was in the high category, while the caries index for permanent teeth (DMFT) in children was in the low category. 25 children who had permanent molars with deep fissures underwent fissure sealant procedures. It can be concluded that this activity has been carried out according to plan. The elementary school students have received promotive and preventive services in the field of dental health, namely providing fissure sealant applications.